Glory be eaudiobook - Arceneaux, Danielle (Glory Broussard, 2023)
The first in a vivid and charming crime series set in the Louisiana bayou, introducing the hilariously uncensored amateur sleuth Glory Broussard. Perfect for fans of Richard Osman's Thursday Murder Club. It's a hot and sticky Sunday in Lafayette, Louisiana, and Glory has settled into her usual after-church routine, meeting gamblers at the local coffee shop, where she works as a small-time bookie. Sitting at her corner table, Glory hears that her best friend—a nun beloved by the community—has been found dead in her apartment. When the police declare the mysterious death a suicide, Glory is convinced that there must be more to the story and, with her reluctant daughter, with troubles of her own, in tow, launches a shadow investigation in a town of oil tycoons, church gossips, and a rumored voodoo priestess. As a Black woman of a certain age who grew up in a segregated Louisiana, Glory is used to being minimized and overlooked. But she's determined to make her presence known as the case leads her deep into a web of intrigue she never realized Lafayette could harbor. Danielle Arcenaux's riveting debut brings for an unforgettable character that will charm and delight crime fans everywhere and leave them hungry for her next adventure.